The Relationships of Intergroup Ideologies to Ethnic Prejudice: A Meta-Analysis. (August 2019) - Whitley, Bernard E.; Webster, Gregory D.
This meta-analysis summarizes the results of research on the relationships of majority group members' endorsement of assimilation, colorblindness, multiculturalism, and the relative relationships of colorblindness and multiculturalism to ethnic prejudice. Random effects analyses found that assimilation was positively related to explicit prejudice ( g . = 0.80), multiculturalism was negatively related to both explicit ( g . = −0.26) and implicit prejudice ( g . = −0.19), and colorblindness was negatively related to explicit prejudice ( g . = −0.07). Multiculturalism was more closely associated with low prejudice than colorblindness ( g. = 0.15). Effect sizes varied as a function of methodology (experimental vs. correlational), country in which research was conducted (United States vs. other countries), and, in experimental studies of multiculturalism, type of prime used (abstract vs. concrete). Discussion points include methodological issues, groups used as targets of prejudice, national diversity norms, additional issues raised in the studies reviewed, and directions for future research.